Tatalaksana Penyinaran Radioterapi 3DCRT Field in Field (FIF) dengan Imobilisasi Thorax Abdomen pada Pasien Kanker Payudara di Unit Radioterapi Rumah Sakit Lavalette Malang - Ni Luh Putu Ema Ardiantari; I Putu Eka Juliantara; Dea Ryangga (Lembaga Pengembangan Kinerja Dosen, 2023)
The 3DCRT field in field (FIF) technique used in Post MRM breast cancer patients at the Radiotherapy Unit at Lavalette Hospital Malang uses 4 copy fields including supraclavicular (AP), axilla (PA), tangential (ML/LM). However, in the Radiotherapy Unit at Lavalette Hospital, Malang, the immobilization device does not use a breast board but uses an abdominal thorax or AIO Breast And Lung Board. The aim of this study is to describe the management or procedures for administering 3DCRT field in field (FIF) radiotherapy with abdominal thorax immobilization in Post MRM breast cancer patients at the Radiotherapy Unit at Lavalette Hospital, Malang. Treatment of 3DCRT field in field (FIF) radiotherapy with abdominal thorax immobilization in Post MRM breast cancer patients at the Radiotherapy Unit at Lavalette Hospital Malang consists of an examination and consultation with a radiation oncology specialist, CT Simulator, then treatment planning system (TPS), verification carried out before the first fraction and participation stage. The advantage of using the 3DCRT field in field (FIF) technique with abdominal thorax immobilization in Post MRM breast cancer patients at the Radiotherapy Unit at Lavalette Hospital, Malang, is that the copying area is simple, the copying comfort is better, it can reduce hotspots, and it can reduce the dose received by the organs in the area. risk (OAR). The disadvantage is that it requires more precision, especially RTT as an operator for the use of additional immobilization devices other than the 5 degree abdominal thorax.